Organizational and contextual support for the promotion of STEM vocations. Psychometrics of a measurement scale (Revista de Investigaciones Universidad del Quindío, 2023)
Introduction: The objective of the study was the psychometric validation of a self-made scale to measure the perception of organizational and contextual support for the promotion of STEM disciplines (science, technology, engineering, and mathematics for its acronym) for high-level student’s upper middle.Method: The questionnaire was administered to paper and pencil anonymously and each participant gave their informed consent at the beginning of the questionnaire. A deterministic sampling was carried out on 390 students who met the inclusion criteria.Results: For content validity, experts were consulted on the subject, and construct validity was estimated by performing an exploratory factor analysis (EFA), using the maximum likelihood factor extraction method with direct oblimin rotation, and reporting loads. factorials greater than 0.5. To validate the theoretical model, a Confirmatory Factor Analysis (CFA) was carried out in the same way, which allowed demonstration of the validity of the previously obtained structure, but with adjustments. The fit indicators of the measurement model were estimated (χ2= 15.20, gl= 8, p > 0.055, SRMR=0.05, AGFI=0.96, RMSEA 0.04 IC90[0.00-0.08], TLI=0.98, and CFI=0.99). , whose values obtained, as well as those of reliability, are considered acceptable according to the standards reported in the literature.Discussion or Conclusion: The measurement model is corroborated with adjustments to the theoretical structure according to what is reported in the adjustment indicators of both exploratory and confirmatory factor analysis. The results present an important contribution in the measurement of the elements that contribute to the promotion of vocations in STEM disciplines. From a methodological perspective, a consistent tool is proposed for the measurement of the defined constructs.
Keywords: STEM; psychometric properties; organizational; contextual support